In prefrontal cortex of rat brain in an experimental psychosis model and the protective effects of melatonin - Ozyurt, B.; Ozyurt, H.; Sahin, S.; Kus, I.; Akyol, O.; Sarsilmaz, M.; Zararsiz, I. (Wiley, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY